2015
DOI: 10.3945/jn.114.202804
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Protein Restriction Increases Respiratory and Sympathetic Activities and Sensitizes Peripheral Chemoreflex in Male Rat Offspring

Abstract: Sympathetic-respiratory overactivity and amplified peripheral chemoreceptor responses, potentially through HIF-1α-dependent mechanisms, precede the onset of hypertension in juvenile rats exposed to protein undernutrition during gestation and lactation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 48 publications
(73 reference statements)
3
50
0
2
Order By: Relevance
“…Experimental models have supported the role of the sympathetic nervous system in the generation of hypertension . Studies have shown that these mechanisms are related to the augmented coupling of the central respiratory network to sympathetic circuits within the ventral medulla, especially in the rostral ventro lateral medulla (RVLM), contributing to sympathetic overactivity and neurogenic hypertension .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental models have supported the role of the sympathetic nervous system in the generation of hypertension . Studies have shown that these mechanisms are related to the augmented coupling of the central respiratory network to sympathetic circuits within the ventral medulla, especially in the rostral ventro lateral medulla (RVLM), contributing to sympathetic overactivity and neurogenic hypertension .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that these mechanisms are related to the augmented coupling of the central respiratory network to sympathetic circuits within the ventral medulla, especially in the rostral ventro lateral medulla (RVLM), contributing to sympathetic overactivity and neurogenic hypertension . Recently, it was reported that rats exposed to protein restriction during pregnancy and lactation exhibited an increase in arterial blood pressure (ABP) associated to sympathetic and respiratory overactivity . However, the mechanisms that predispose offspring to hypertension and augmentation of sympathetic‐respiratory activities in the maternal diet induced‐hypertension model are as yet poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Other research has shown that impaired renal function contributes to augmentation of blood pressure in rats exposed to protein malnutrition during pregnancy and/or lactation . More recently, our laboratory demonstrated that the development of hypertension in rats exposed to protein restriction during pregnancy and lactation is associated with sympathetic hyperactivity …”
Section: Introductionmentioning
confidence: 70%
“…Nowadays, it is well accepted that perinatal protein malnutrition raise risks of hypertension by mechanisms that include abnormal vascular function (Franco Mdo et al, 2002; Brawley et al, 2003; Franco et al, 2008), altered nephron morphology and function, and stimulation of the renin-angiotensin system (RAS) (Nuyt and Alexander, 2009; Siddique et al, 2014). Recently, studies have highlighted contribution of the sympathetic overactivity associated to enhanced respiratory rhythm and O 2 /CO 2 sensitivity on the development of the maternal low-protein diet-induced hypertension by mechanisms independent of the baroreflex function (Chen et al, 2010; Barros et al, 2015; Costa-Silva et al, 2015; de Brito Alves et al, 2015; Paulino-Silva and Costa-Silva, 2016). Offspring from dams subjected to perinatal protein restriction had relevant short-term effects on the carotid body (CB) sensitivity and respiratory control.…”
Section: Maternal Protein Undernutrition: Early- and Long-term Outcomesmentioning
confidence: 99%
“…Offspring from dams subjected to perinatal protein restriction had relevant short-term effects on the carotid body (CB) sensitivity and respiratory control. With enhanced baseline sympathetic activity and amplified ventilatory and sympathetic responses to peripheral chemoreflex activation, prior to the establishment of hypertension (de Brito Alves et al, 2014, 2015). The underlying mechanism involved in these effects seems to be linked with up-regulation of hypoxic inducible factor (HIF-1α) in CB peripheral chemoreceptors (Ito et al, 2011, 2012; de Brito Alves et al, 2015).…”
Section: Maternal Protein Undernutrition: Early- and Long-term Outcomesmentioning
confidence: 99%